Hooliganism in Gabon: African exception or Gabonese particularities? - Dominique, Bodin; Sophie, Javerlhiac; Axel, Augé; Stéphane, Héas (Advances in Social Sciences Research Journal, 2019)
African football has been dynamic for many decades. Hooliganism is also present on this continent. While all other countries are affected by acts of hooliganism, Gabon has been spared from this type of sports violence until very recently. The political instrumentalization of football, its use as a "modern watchtower", but also its use as an educational vehicle, have contributed to both the enthusiasm for the game and the framing of the game. The apologetic function of this practice appears exemplary here, although weakened by the political oppositions that undermine the country. While there is no "traditional" hooliganism, the violence surrounding the national team's results questions the political role of this sport in the country.